Pengaruh Citra Negara Asal terhadap Keputusan Pembelian Mellaui Citra Merek (Studi pada Konsumen Mobil Wuling di Kota Semarang) - Hasmoro, Alexander Dio; Darmastuti, Ismi; Nurdianasari, Rista (Diponegoro Journal of Management, 2024)
ABSTRACT Sales of the car industry in Indonesia can be said to be growing rapidly in the last period. The car brand used as the object of this study is Wuling, which is a vehicle brand from Liuzhou, Guangzi, China. This brand is run by the Liuzhou Wuling Automobile Industry, Co., Ltd. company, which is a joint venture by Wuling Group and Dragon Hill Holdings Limited. This research was conducted in Semarang City which resulted in preresearch in the form of low purchasing decisions, namely there are indications of problems regarding the purchasing decisions of Wuling consumers in Semarang City in the indicators "My need for Wuling cars is high", "I feel that the number of products issued by Wuling cars is varied and has many types", and "I will buy Wuling car products again in the future" which the majority stated "no". This study used Wuling consumers in Semarang City as the research population, then sampling was carried out using purposive sampling and had several criteria. The sample in this study amounted to 150 respondents with the criteria of having made a decision to buy a Wuling car at least 1 type of car and domiciled in Semarang City. The collected data were analyzed using the structural equation model (SEM) method and processed with AMOS software. The results of this study show that country of origin has a significant positive effect on purchasing decisions, brand image has a significant positive effect on purchasing decisions, and country of origin has a significant positive effect on brand image.